2014
DOI: 10.5194/acpd-14-1791-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of surface and column measurements of aerosol scattering properties over the western North Atlantic Ocean at Bermuda

Abstract: Abstract. Light scattering and spectral absorption by size-resolved aerosols in near-surface air at Tudor Hill, Bermuda were measured continuously between January and June 2009. Vertical distributions of aerosol backscattering and column-averaged aerosol optical properties were characterized in parallel with a Micro-pulse lidar (MPL) and an automated sun-sky radiometer. Aerosol optical properties measured near the surface were often significantly correlated with those averaged over the column. These include sc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…8 and Table 2; (ii) AERONET data are representative of ambient conditions, and changes in relative humidity can influence VSD profiles; and (iii) AERONET data are column-based and not necessarily representative of only the surface layer where the trajectories end in our analysis of HYSPLIT data. Related to the last point, past work noted that column optical properties over Bermuda can be weakly correlated with such measurements at the surface (Aryal et al, 2014) due largely to aerosol layers aloft (Ennis and Sievering, 1990). At the same time, studies have shown that there can be enhanced number and volume concentrations in the marine boundary layer versus the free troposphere over Bermuda (Horvath et al, 1990;Kim et al, 1990).…”
Section: Volume Size Distributionsmentioning
confidence: 95%
“…8 and Table 2; (ii) AERONET data are representative of ambient conditions, and changes in relative humidity can influence VSD profiles; and (iii) AERONET data are column-based and not necessarily representative of only the surface layer where the trajectories end in our analysis of HYSPLIT data. Related to the last point, past work noted that column optical properties over Bermuda can be weakly correlated with such measurements at the surface (Aryal et al, 2014) due largely to aerosol layers aloft (Ennis and Sievering, 1990). At the same time, studies have shown that there can be enhanced number and volume concentrations in the marine boundary layer versus the free troposphere over Bermuda (Horvath et al, 1990;Kim et al, 1990).…”
Section: Volume Size Distributionsmentioning
confidence: 95%
“…A subset of the field studies described up until now have included some degree of attention toward Bermuda, but here we focus on those studies that were more intimately linked to the island and the adjacent Sargasso Sea (Figure ). Research activities have been intense at Bermuda over past decades as it represents a site ideal for long‐term data relevant to climate and atmospheric changes (e.g., Aryal et al, ). The long‐term nature of measurements available at Bermuda has allowed for specific lines of inquiry that would not be possible with short‐term data sets.…”
Section: History Of Bermuda and Sargasso Sea Researchmentioning
confidence: 99%
“…A few aerosol studies are worth noting that examined issues other than reporting chemical composition and sources. Aerosol scattering was characterized by Aryal et al (), showing that columnar optical properties are weakly related to surface optical properties, motivating the importance of vertically resolved measurements. The acidity of regional aerosols was characterized at Bermuda in multiple studies (Keene, Pszenny, et al, ; Keene & Savoie, ); Keene, Pszenny, et al () showed that supermicrometer particles, mainly composed of sea salt, exhibited pHs in the upper 3s and 4s, whereas finer aerosols had pHs in the 1s and 2s.…”
Section: History Of Bermuda and Sargasso Sea Researchmentioning
confidence: 99%
“…North American pollution and outflow over the WNAO have been of interest for reasons such as acid rain (e.g., Cogbill & Likens, 1974; Likens & Bormann, 1974) and the opportunity to examine the aging of gas and aerosol pollutants (e.g., Fehsenfeld et al., 2006). Bermuda in particular has been a scientifically critical island where an extensive amount of research has been conducted over the last several decades to monitor changes in variables associated with pollution, climate, and general atmospheric changes (Aryal et al., 2014; Keene et al., 2014). The Sargasso Sea around Bermuda has also been the subject of many efforts intended to examine air‐sea interaction processes, aerosol deposition, ocean biogeochemistry, and primary marine aerosol fluxes (Beaupre et al., 2019; Frossard et al., 2019; Lomas et al., 2013; Michaels & Knap, 1996; Steinberg et al., 2001; X. L. Zhou et al., 2008).…”
Section: Introductionmentioning
confidence: 99%